The Maintenance of Peace in Mozambique: From GPA to the First Multiparty Elections, 1992-1994 - Gujamo, Rufino Carlos (Cultural and religious studies, 2019)
After sixteen years of civil war the Mozambican government led by the Mozambique Liberation Front (FRELIMO) and the Mozambican National Resistance (RENAMO) have signed the General Peace Agreement (GPA) in Rome, Italy, on 4th October 1992. The agreement that ended the war resulted from a negotiation process initiated following the hurting stalemate situation between the two conflicting parties. In the context of the implementation of such agreement the country experienced, successfully, the first multiparty elections in 1994 with the participation of FRELIMO and RENAMO - former military enemies as well as other political parties without any case of war resumption. This article seeks to identify the determinants factors for peace maintenance in Mozambique from the General Peace Agreement (GPA) to the first multiparty elections. Besides the important support provided by the international community, this article argues that the implementation of power sharing arrangements established in the context of GPA, namely, (1) military power sharing, (2) administrative and territorial power sharing, and (3) power sharing within the electoral institutions played an important role for peace maintenance in Mozambique during the period mentioned above.